Using journal use study feedback to improve accessibility - Zainab, Awang Ngah; Huzaimah, A.R.; Ang, T.F. (Emerald, 2007)
The purpose of this research is to examine users preference and use of electronic journals in general, especially those published in a hosting system, Electronic Journal of the University of Malaya (EJUM) Design/methodology/approach - The study utilized the survey method and employed an online questionnaire as the data collection instrument. A list of 330 users who registered with EJUM was selected and an e-mail was sent to each with an invitation to complete the survey form linked to their mail. A total of 140 responses were returned, out of which 102 responses were usable. Findings - The electronic journals are used for searching new information, reading full-text articles, reading abstracts, and browsing the table of contents. Users are led to EJUM by chance while browsing the internet (41.8 per cent) when searching using Google, through citations obtained from conference papers, from articles or citations in databases. About 50 per cent of respondents rated the journals as "good" and 20.6 per cent rated "fair". Respondents prefer keywords (28.9 per cent) and title (24.3 per cent) searches. The majority of respondents (70 per cent) prefer articles in PDF. The majority of respondents read the abstracts first to determine relevance before downloading the articles. Respondents believe that electronic journals will either co-exist with print journals (46.2 per cent) or replace the print journals (25.5 per cent) or supplement (25.5 per cent) them. Users indicate the functions and features preferred in electronic journals. Practical implications/limitations - A HTML indexing page is created to automatically harvest the meta labels from the contents pages of journal issues, which is captured by Googlebot of Google Scholar. This strategy improves accessibility as Google Scholar provides citation and publication counts for articles and authors. A quality matrix for an electronic journal system is presented Originality/value - The study shows the extent to which e-journals are used in Malaysia and provides a matrix of usability features which potential electronic journal publishers could consider.